Cardiorespiratory fitness, different measures of adiposity, and serum vitamin D levels in African-American adults. (October 2019) - Farrell, Stephen William; DeFina, Laura; Willis, Benjamin; Barlow, Carolyn E; Pavlovic, Andjelka; Leonard, David; Haskell, William
We examined the associations among cardiorespiratory fitness (CRF), adiposity, and serum 25-hydroxyvitamin D [25(OH)D) levels in African-American (AA) adults. 468 AA patients from the Cooper Clinic in Dallas, TX were examined between 2007 and 2018. Measures included body mass index (BMI), waist circumference (WC), percent body fat (%fat) via skinfolds, CRF via a maximal treadmill test, and 25(OH)D. Participants were classified by CRF based on age and sex, as well as by clinical categories of adiposity exposures and 25(OH)D. We examined trends of 25(OH)D across CRF and adiposity categories. We calculated OR with 95% CIs for 25(OH)D deficiency across categories of CRF and adiposity measures. We observed a significant positive trend for CRF (p=0.01) and a significant inverse trend for BMI (p=0.005) across ordered 25(OH)D categories. Adjusted mean 25(OH)D levels were higher across ordered CRF categories (p=0.03), and lower across ordered categories of BMI (p=0.02), WC (p=0.03) and %fat (p=0.04). When grouped into categories of fit and unfit (upper 80% and lower 20% of the CRF distribution, respectively), OR for vitamin D deficiency was significantly lower in fit compared with unfit men and women (OR=0.55, 95% CI: 0.35–0.87, p=0.01). Compared with normal weight BMI (referent), ORs for 25(OH)D deficiency were significantly higher for BMI-obese subjects (OR=1.70, 95% CI: 1.00–2.87, p=0.04). 25(OH)D levels are positively associated with CRF and negatively associated with different measures of adiposity in AA men and women. Because of the study design, causal inferences cannot be made and future prospective studies are needed.